Analysis of the Utilization of Information Technology, Competency and Organizational Culture with Work Motivation as Intervening Variables on the Performance of Lecturers at Sekolah Tinggi Ilmu Ekonomi Mandala - Difari Afreyna Fauziah; Purnamie Titisari; Nurhayati Nurhayati (Budapest International Research and Critics University, 2022)
This study aims to examine and analyze the direct and indirect effects of the use of information technology, competence and organizational culture through work motivation on the performance of lecturers at STIE Mandala Jember. This research was conducted on permanent lecturers at STIE Mandala Jember. The number of respondents in this study were 39 people. The sampling technique used is a saturated sample in which the entire population in the study is sampled. Data analysis was carried out usingPartial Least Square - Structural Equation Model (PLS-SEM). HasThe research shows that the use of information technology, competence and work motivation has a significant positive effect on lecturer performance, while organizational culture has no significant effect on lecturer performance.